Pemanfaatan Literasi Digital Dalam Kesiapan Guru Mengajar Mata Pelajaran Sejarah Kebudayaan Islam - Rizkha Diana Akmalia; Hasanah Hasanah (An-Nuha, 2024)
This research is based on the fact that studying the History of Islamic Culture lesson is generally very boring, and students are rarely interested in the History of Islamic Culture lesson. This is where subject teachers are required to be creative in packaging learning material so that it looks interesting and not boring. Nowadays, the delivery of material is not only done by lecturing, where the teacher provides all the information to the students, by speaking at length in front of the students, but teachers can also use computers and the like to help convey the material to the students. The aim of this thesis research is to know the use of digital literacy in teachers' readiness to teach the History of Islamic Culture subject during the even semester of the 2023/2024 academic year with digital literacy in Class IV MI Mumtaza Islamic School, South Tangerang. The research method used in this research is a qualitative approach with descriptive analysis research type, then using data collection techniques in the form of classroom observations, interviews with teachers, principals, students, and analysis of several required documents. The data analysis technique uses data reduction from Miles and Huberman. The results of the research show that the use of digital literacy in understanding Islamic Cultural History learning at MI Mumtaza Islamic School is going well, with research evidence as follows: That the use of digital literacy at MI Mumtaza Islamic School has been maximized, starting from searching for SKI materials. In its application, teachers use social media as a material for searching for information and knowledge about SKI, teachers direct students to find out more knowledge through digital media, teachers have the ability to assess SKI material, teachers are able to form knowledge through digital media.